32. RESEARCH ON SOME SIDE EFFECTS IN CHILDREN AFTER THE FIRST DOSE OF COVID-19 VACCINATION AT THE PEDIATRIC CENTER OF BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objective: To describe side effects impact on children after the first dose of an mRNA Covid-19 vaccine injection at the pediatric center of Bach Mai Hospital. Subject and methods: A descriptive study was conducted on 61 children ages 12 years after the first dose of an mRNA Covid-19 vaccine injection had clinical symptoms admitted to the pediatric center of Bach Mai Hospital. Results: The study collected 61 children, including 32 females and 29 males. The male/female ratio was 0,9/1. The most common symptom onset time is 2-7 days after vaccination, with a rate of 52.5%. The most typical clinical symptoms are chest pain (52.5%), shortness of breath 32.8%, fatigue 29.5%, and other clinical symptoms such as fever, dizziness, nausea, palpitations, and headache. There were 7 patients with anaphylaxis accounting for 11.5%, of which 3 patients had grade 3 anaphylaxis, accounting for 4.9%. The most common subclinical symptom is leukocytosis, which accounts for 9/50 children, 18% of which have an increased Troponin T index, an average Troponin index of 63.07±182 ng/l, there are 5 /61 accounted for 8.2% of patients had arrhythmia, 8/61 had ST elevation on electrocardiogram, accounting for 13.1%. Conclusion: Clinical and subclinical symptoms of children over 12 years old are usually mild, moderate and fast recover after treatment.
Keywords: Covid-19, mRNA Covid-19 vaccine, children aged 12-17.